Sedimentary indicators of a deep sea environment, in the sandstones of rocky forms, from the Ciężkowice-Rożnów Landscape Park (Outer Carpathians) // Świadectwa środowisk głębokomorskich w piaskowcach skałek Ciężkowicko-Rożnowskiego Parku Krajobrazowego - Stadnik, Renata; Waśkowska, Anna (Geotourism/Geoturystyka, 2018)
The rocky forms of the Ciężkowice-Rożnów Landscape Park form the remains of the solid cover of the Ciężkowice Sandstone. Deposits in rocky forms represent different types of facies. Numerous and genetically diverse sedimentary structures in the sandstones are typical for a deep-sea flysch environment. Analysis of these well preserved features makes it possible to interpret the paleoenvironment of their sedimentation in the Eocene. These features have also become unusually valuable, in terms of both research methodology, known as sedimentological facies analysis, as well as in popularising geological knowledge. // Skałki Ciężkowicko-Rożnowskiego Parku Krajobrazowego są obiektami, które pozostały po zwartym kompleksie piaskowca ciężkowickiego. Na ich powierzchniach czytelne są liczne i zróżnicowane genetycznie struktury sedymentacyjne oraz litofacje, które są typowe dla fliszowych środowisk głębokomorskich. Stopień wyrazistości tych struktur na powierzchniach skałek jest wysoki, dlatego stanowią one nie tylko obiekty cenne dla interpretacji paleośrodowisk, ale również cenne dla popularyzacji wiedzy geologicznej.